Differences in the gut microbiome by physical activity and BMI among colorectal cancer patients - Himbert, Caroline; Stephens, W Zac; Gigić, Biljana; Hardikar, Sheetal; Holowatyj, Andreana N; Lin, Tengda; Ose, Jennifer; Swanson, Eric; Ashworth, Anjelica; Warby, Christy A; Peoples, Anita R; Nix, David; et al. (American journal of cancer research, 2022)
Associations of energy balance components, including physical activity and obesity, with colorectal cancer risk and mortality are well established. However, the gut microbiome has not been investigated as underlying mechanism. We investigated associations of physical activity, BMI, and combinations of physical activity/BMI with gut microbiome diversity and differential abundances among colorectal cancer patients.
Der Artikel hat keinen DOI
Das PDF enthält zusätzlich einen Anhang von 8 Seiten
Gesehen am 17.01.2023